An optimized SEC‐SAXS system enabling high X‐ray dose for rapid SAXS assessment with correlated UV measurements for biomolecular structure analysis. Issue 1 (3rd January 2018) - Ryan, Timothy M.; Trewhella, Jill; Murphy, James M.; Keown, Jeremy R.; Casey, Lachlan; Pearce, F. Grant; Goldstone, David C.; Chen, Kelan; Luo, Zhenyao; Kobe, Bostjan; McDevitt, Christopher A.; Watkin, Serena A.; et al.
Abstract : Size exclusion chromatography (SEC) small‐angle X‐ray scattering (SAXS) is a powerful structural biology tool where the best outcomes are obtained through an optimized experimental approach. Optimization of SEC and integration of a sheath flow sample environment into the Australian Synchrotron's SAXS/WAXS beamline has greatly improved data quality and the ability to deal with difficult protein samples. Abstract : A new optimized size exclusion chromatography small‐angle X‐ray scattering (SEC‐SAXS) system for biomolecular SAXS at the Australian Synchrotron SAXS/WAXS beamline has been developed. The compact configuration reduces sample dilution to maximize sensitivity. Coflow sample presentation allows an 11‐fold increase in flux on sample without capillary fouling, improving throughput and data quality, which are now primarily limited by the full flux available on the beamline. Multi‐wavelength fibre optic UV analysis in close proximity to the X‐ray beam allows for accurate concentration determination for samples with known UV extinction coefficients and thus estimation of the molecular weight of the scattering particle from the forward X‐ray scattering intensity. Fast‐flow low‐volume SEC columns provide sample throughput competitive with batch concentration series measurements, albeit with a concomitant reduction of potential resolution relative to lower flow rates and larger SEC columns. The performance of the system is demonstrated using a set of model proteins, and its utility to solve various challenges is illustrated with a diverse suite of protein samples. These developments increase the quality and rigor of SEC‐SAXS analysis and open new avenues for biomolecular solution SEC‐SAXS studies that have been challenged by low sample yields, temporal instability, radiation sensitivity and complex mixtures.